Chemokine MCP1 is associated with cognitive flexibility in schizophrenia: A preliminary analysis. (June 2021) - Klaus, Federica; Mitchell, Kyle; Liou, Sharon C.; Eyler, Lisa T.; Nguyen, Tanya T.
Abstract: Background: Peripheral levels of pro-inflammatory biomarkers have been shown to be altered in schizophrenia (SZ) and associated with cognitive impairments, but their relevance to specific cognitive domains remains unclear. Methods: Plasma levels of cytokines, chemokines, and vascular biomarkers were quantified and compared between SZ and healthy comparison (HC) groups. Cognition was assessed using the Delis-Kaplan Executive Function System Trail Making (TM) and Color Word Interference (CWI) tests. Linear regression analyses examined differential relationships of inflammatory biomarkers with executive function between groups. Results: Plasma levels of TNFα, ICAM1, and MCP1 were higher in individuals with SZ compared to HCs. Higher level of MCP1 was associated with increased CWI Inhibition Switching Errors in SZ but not HCs. Conclusion: Like other studies, we found evidence for increased peripheral inflammation in SZ. We also showed that SZ with particularly high MCP1 levels had poor cognitive flexibility. Interventions to reduce chemokine elevations might prove beneficial for cognitive performance.